The development of socio-productive in family farming associations in the amazonica region - Schimith, Cristiano Descovi; Alves, João Victor Reis; Fonseca, Roberta Carolina Salgado (Revista de Administração da UFSM, 2018)
The family farming features the management of shared resources, the source of income, productive diversity, workplaces and farmers dwellings, thus develop socio-productive bring progress for the economy, mainly by promoting entrepreneurship among the associations. Therefore, this research aims to analyze the panorama of associations of family agriculture in the municipalities of Abaetetuba, Ananindeua, Barcarena, Belém and Santa Izabel, in order to identify demands and propose socio-productive actions management and accounting, promoting the development of Social Entrepreneurship in the Amazon region. To this end, a research Participant of qualitative and exploratory objective to identify the local demands of the associations surveyed was carried out. The results show that when identifying the demands and consequently perform the socio-productive actions, the members showed more participatives, developing entrepreneurial actions, have improved the deal and the responsibility of the financial budget familiar, presented more interest in developing entrepreneurial actions among the joins that consequently qualified for obtaining public calls, thus contributing to local sustainable development.